Absence of ATFL Remnant Does not Affect the Clinical Outcomes of the Modified Broström Operation for Chronic Ankle Instability. Issue 4 (16th October 2019) - Park, Sunghoon; Kim, Taehun; Park, Younguk
Category: Ankle, Arthroscopy, Sports Introduction/Purpose: The modified Broström operation (MBO) for chronic ankle instability (CAI) has demonstrated good clinical results. Absence of ligamentous tissue was known as a risk factor for recurrence of ankle instability after the sugery. The aim of this study was to evaluate the effect of quality of ligament tissue (anterior talofibular ligament, ATFL) on prognosis in a cohort of patients with CAI after the MBO. Methods: This study was a retrospective case series. A total of 60 patients underwent the MBO for CAI with a mean follow-up of 30.1 months (range, 24-47 months). Presence of ATFL remnant was assessed on ultrasound (US), magnetic resonance imaging (MRI), and arthroscopy in all patients. The foot and ankle outcome score (FAOS) was used to evaluate functional outcomes. Clinical outcomes were compared according to the condition of the ligament remnant. Association with other risk factors was evaluated using multiple linear regression analysis. Results: ATFL was visible in 51/60 cases on US. Thirty patients had thin or absent ATFL on MRI; 22 patients, normal thickness ATFL; and 8 patients, thick ATFL. ATFL was visible in 15 patients on arthroscopy and nonvisible or not clear in 45 cases. Significant differences in FAOS were not noted according to the presence of ATFL remnant on US, arthroscopy, and the grade of ATFL thickness on MRI. No correlation was found between FAOS and the thickness of ATFL. Conclusion: The results suggest that the MBO for patients with CAI had good results, regardless of the presence or absence of ATFL remnant.